2016
DOI: 10.3892/ol.2016.5112
|View full text |Cite
|
Sign up to set email alerts
|

NaHCO3 enhances the antitumor activities of cytokine-induced killer cells against hepatocellular carcinoma HepG2 cells

Abstract: The extracellular pH is lower inside solid tumors than in normal tissue. The acidic environment inhibits the cytotoxicity of lymphocytes in vitro and promotes tumor cell invasion. In the present study, both in vitro and in vivo experiments were conducted to investigate how NaHCO3 would affect the antitumor activities of cytokine-induced killer (CIK) cells against hepatocellular carcinoma (HCC) cells. For the in vitro experiments, HepG2 cells were cultured at pH 6.5 and 7.4 in the presence of CIK cells or CIK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The pH-regulating injectable hydrogel platforms such as the one presented here can potentially improve the uptake of other weak base chemotherapeutics that are susceptible to ion trapping, reducing harmful side effects from a high dosage. In addition, due to rising evidence of the negative impact of acidosis on immune evasion, similar pH-regulating hydrogel platforms can be used to improve immunotherapy outcomes. …”
Section: Discussionmentioning
confidence: 99%
“…The pH-regulating injectable hydrogel platforms such as the one presented here can potentially improve the uptake of other weak base chemotherapeutics that are susceptible to ion trapping, reducing harmful side effects from a high dosage. In addition, due to rising evidence of the negative impact of acidosis on immune evasion, similar pH-regulating hydrogel platforms can be used to improve immunotherapy outcomes. …”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, pre-clinical studies showed the relevance of combined therapies based on inhibition of lactate release, or generic anti-acidic strategies, associated with immune therapies to counteract tumor progression [119,125,172,173].…”
Section: Resultsmentioning
confidence: 99%
“…104,180 Accordingly, different buffering approaches such as the administration of bicarbonate or proton pump inhibitors (PPIs) promoted immunotherapy. [181][182][183] Moreover, Vishvakarma and collegues showed that the application of PPIs resulted in an enhanced recruitment of M1 macrophages and shifted the cytokine profile toward tumor cytotoxic cytokines. Finally, this study showed that macrophages isolated from PPI treated tumors, which were adoptively transferred in tumor-bearing mice, showed superior capacity to control tumor growth.…”
Section: Targ E Ting the Warburg Effec T For Tumor Ther Apy And Immmentioning
confidence: 99%
“…Buffering, therefore, might be an alternative strategy to reduce the negative effects of tumor acidification not interfering with immune cell activation . Accordingly, different buffering approaches such as the administration of bicarbonate or proton pump inhibitors (PPIs) promoted immunotherapy . Moreover, Vishvakarma and collegues showed that the application of PPIs resulted in an enhanced recruitment of M1 macrophages and shifted the cytokine profile toward tumor cytotoxic cytokines.…”
Section: Targeting the Warburg Effect For Tumor Therapy And Immune Acmentioning
confidence: 99%